2017
DOI: 10.1001/jamainternmed.2017.3133
|View full text |Cite
|
Sign up to set email alerts
|

Progress Toward Universal Health Coverage

Abstract: IMPORTANCEAchieving universal health coverage is one of the key targets in the newly adopted Sustainable Development Goals of the United Nations.OBJECTIVE To investigate progress toward universal health coverage in 5 South Asian countries and assess inequalities in health services and financial risk protection indicators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 30 publications
0
30
0
Order By: Relevance
“…While each country must decide its own path towards UHC based on the individual country contexts, all should draw on existing evidence and shared experience. Currently available evidences from Bangladesh on UHC mostly include quantitative household surveys on out of pocket expenditure [14,15], financial risk protection [6,[15][16][17], and equity analysis [6,[16][17][18]. The policy environment around UHC issues has been analyzed by very few studies, which includes an assessment of a set of proposed indicators related to UHC [19,20], and generic policy papers without description of methodology [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…While each country must decide its own path towards UHC based on the individual country contexts, all should draw on existing evidence and shared experience. Currently available evidences from Bangladesh on UHC mostly include quantitative household surveys on out of pocket expenditure [14,15], financial risk protection [6,[15][16][17], and equity analysis [6,[16][17][18]. The policy environment around UHC issues has been analyzed by very few studies, which includes an assessment of a set of proposed indicators related to UHC [19,20], and generic policy papers without description of methodology [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Not only financing and institutionalization are critical for achieving UHC, but also measuring progress towards UHC is equally important. The three core dimensions of UHC proposed by the WHO 8 are “the proportion of a population covered by existing healthcare systems, the range of healthcare services available to a population, and the extent of financial risk protection available to local populations” 9 . An analysis of South Asian countries reported that access to basic care varied substantially within and across each country.…”
mentioning
confidence: 99%
“…An analysis of South Asian countries reported that access to basic care varied substantially within and across each country. In India, financial risk protection was only 17.9 per cent and prevention and treatment coverage for selected heath conditions was 83.5 per cent 9 . The study also raised equity concerns, highlighting that access to care for maternal and child health services was higher among rich as compared to poor mothers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…With these new challenges, we see inequalities forming along the same old social fault lines and the same axes of deprivation and discrimination. In high-income countries, new risk factors such as obesity and food insecurity cluster in the poorest communities [3,4], while on a global level, we see the greatest burden of new diseases such as HIV falling on the poorest countries [5], and continuing challenges of health access and financing for the poorest people [6]. Much of this inequality arises from simple economic inequality and the consequences of colonialism, but much also results from the marginalization of certain individuals and groups at community, national and global levels.…”
mentioning
confidence: 99%